An Educational Intervention for Acute Dizziness Care: A Randomized, Vignette-based Study. Issue 8 (September 2019) - Meurer, William J.; Johnson, Patricia; Brown, Devin; Tsodikov, Alexander; Rowell, Brigid; Fagerlin, Angela; Telian, Steven A.; Damschroder, Laura; An, Lawrence C.; Morgenstern, Lewis B.; Kerber, Kevin A.
Abstract : Importance: Benign paroxysmal positional vertigo (BPPV) is a common cause of acute dizziness. Strong evidence exists for diagnosing BPPV using the Dix-Hallpike Test (DHT) and treating it with the canalith repositioning maneuver (CRM). Despite this, both are infrequently used in the emergency department (ED). Objective: As an early method to evaluate a BPPV-focused educational intervention, we evaluated whether an educational intervention improved ED provider performance on hypothetical stroke and BPPV cases delivered by vignette. Design: A randomized, controlled, educational intervention study in ED physicians. The intervention aimed to promote the appropriate use of the DHT and CRM. A BPPV vignette, a stroke-dizziness (safety) vignette, and vignette scoring schemes (higher scores indicating more optimal care) used previously established vignette methodology. Setting: We recruited participants at the exhibitor hall of an emergency medicine annual meeting. Participants: We recruited 48 emergency physicians. All were board certified or residency trained and board eligible. All were engaged in the active practice of emergency medicine. None were trainees. Interventions: Intervention group: a narrated, educational presentation by computer followed by the clinical vignettes. Control group: Received no educational intervention and completed the clinical vignettes—intended to mirror current clinician practice. Main Outcome Measure: Primary endpoint: total score (out of 200 points) on a vignette-based scoring instrument assessing the performance of history, physical, and diagnostic testing on hypothetical stroke and BPPV cases. Results: The efficacy threshold was crossed at the interim analysis. The intervention group had higher performance scores compared with controls (113.2 versus 68.6, p < 0.00001). BPPV and safety subscores were both significantly higher in the intervention group. Sixty-two percent of the intervention group planned to use the DHT versus 29% of controls. After the vignette described characteristic BPPV nystagmus, 100% of the intervention group planned to use the CRM versus 17% of controls. Conclusions and Relevance: The educational intervention increased provider performance in dizziness vignettes, including more frequent appropriate use of the DHT/CRM. These findings indicate the intervention positively influenced planned behavior. Future work is needed to implement and evaluate this intervention in clinical practice. Abstract : Supplemental Digital Content is available in the text